Pertumbuhan Semai Jabon (Anthocephalus cadamba Roxb. Miq.) pada Media Tailing PT ANTAM Unit Bisnis Pongkor dengan Penambahan Top Soil dan Kompos - Basuki Wasis; Yadi Setiadi; Hafizah Br Tarigan (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2011)
Growth of Jabon (Anthocephalus cadamba Roxb. Miq.) on PT ANTAM Unit Bisnis Pongkor’s Tailing with Top Soil and Compost AdditionGold tailing has some characteristics such as low of organic material and microorganism activity, deficient in nutrition andlow of CEC (cation exchange capacity). This constraint to revegetation, therefor soil amandment needed before revegetation program. Top soil and compost addition, which can improve soil condition and nutrition, also as microbe source.It is necessary to select tree species for revegetation post mining activity. Pioneer species that chosen have to well adaptive, fast growing, known silviculture techniques, available in plant resource, microbial symbiosis and catalytic. One of the potential species is jabon (Anthocephalus cadamba Roxb. Miq.). The result of this research is growth respon of jabon on tailing with top soil and compost addition can improve growth of tall, stem diameter and root biomass. The best dose combination are 20 grams compost combine with 250 grams top soil.